A large, multi-centre prospective study demonstrating high prevalence of malnutrition associated with reduced survival in ambulatory systemic anti-cancer therapy patients. (December 2022) - Sullivan, Erin Stella; Daly, Louise E.; Scannell, Clodagh; Ní Bhuachalla, Éadaoin B.; Cushen, Samantha; Power, Derek G.; Ryan, Aoife M.
Summary: Background & aims: The nutritional status of cancer patients is highly variable, and known to impact on clinical outcomes. To date, no large study evaluating the nutritional status of Irish cancer patients has been reported. The aim of this study was to describe the nutritional status, using gold standard methods, of a large cohort of ambulatory oncology patients receiving Systemic Anti-Cancer Therapy and to assess the impact of abnormal body composition phenotypes on survival. Methods: A prospective study in adults undergoing Systemic Anti-Cancer Therapy for solid tumours enrolled patients between 2012 and 2016. Baseline details were collected incorporating demographics, cancer pathology, lifestyle, body composition (by computed tomography (CT), and inflammatory status. Skeletal muscle index (SMI) and mean muscle attenuation (MA) were obtained from CT images and categorised to low muscle mass and low MA using previously published sex specific cut points. Survival was monitored for a median of 25 months [IQR:10–46 months]. Survival analyses were conducted using multivariate Cox Proportional Hazards Models. Results: Of 1015 patients recruited, 940 patients with an evaluable CT were included in this analysis. Median age was 64 years [IQR 55–71] and 56% were male. Colorectal cancer (28%) and gastro-oesophageal (16%) were the most common diagnoses and 58% of patients had stage IV disease. Despite 56% being overweight or obese (BMI >25 kg/m 2 ), 52% were weight losing and 17% had lost >10% body weight. Cancer Cachexia (CC) was present in 42%, 39% had low muscle mass (MM) (sarcopenia) and 45% had low MA. Overall, 73% of patients exhibited an abnormal body composition (BC) phenotype (≥1 of CC, low MM/MA). Overall survival was significantly lower in those with abnormal BC phenotype, independent of site, stage, sex, ECOG and mGPS (HR: 1.416 [95% CI: 1.069–1.875], p  = 0.015). Conclusions: Malnutrition and abnormal body composition phenotypes are common in cancer, but are often masked by adiposity. Appropriate screening and diagnostic tools should consider this co-presentation of overweight and obesity, alongside muscle depletion. Given that abnormal body composition phenotypes detectable only via CT are associated with reduced survival, these should be more widely employed to identify patients at risk of poor prognosis, and allow potentially more effective, early intervention.